let n be Nat; :: thesis: for K being Field

for M1, M2 being Matrix of n,K st M1 is invertible holds

M2 * M1 is_similar_to M1 * M2

let K be Field; :: thesis: for M1, M2 being Matrix of n,K st M1 is invertible holds

M2 * M1 is_similar_to M1 * M2

let M1, M2 be Matrix of n,K; :: thesis: ( M1 is invertible implies M2 * M1 is_similar_to M1 * M2 )

A1: ( len M2 = n & width (M1 ~) = n ) by MATRIX_0:24;

assume A2: M1 is invertible ; :: thesis: M2 * M1 is_similar_to M1 * M2

then A3: M1 ~ is_reverse_of M1 by MATRIX_6:def 4;

take M1 ; :: according to MATRIX_8:def 5 :: thesis: ( M1 is invertible & M2 * M1 = ((M1 ~) * (M1 * M2)) * M1 )

( len M1 = n & width M1 = n ) by MATRIX_0:24;

then ((M1 ~) * (M1 * M2)) * M1 = (((M1 ~) * M1) * M2) * M1 by A1, MATRIX_3:33

.= ((1. (K,n)) * M2) * M1 by A3, MATRIX_6:def 2

.= M2 * M1 by MATRIX_3:18 ;

hence ( M1 is invertible & M2 * M1 = ((M1 ~) * (M1 * M2)) * M1 ) by A2; :: thesis: verum

for M1, M2 being Matrix of n,K st M1 is invertible holds

M2 * M1 is_similar_to M1 * M2

let K be Field; :: thesis: for M1, M2 being Matrix of n,K st M1 is invertible holds

M2 * M1 is_similar_to M1 * M2

let M1, M2 be Matrix of n,K; :: thesis: ( M1 is invertible implies M2 * M1 is_similar_to M1 * M2 )

A1: ( len M2 = n & width (M1 ~) = n ) by MATRIX_0:24;

assume A2: M1 is invertible ; :: thesis: M2 * M1 is_similar_to M1 * M2

then A3: M1 ~ is_reverse_of M1 by MATRIX_6:def 4;

take M1 ; :: according to MATRIX_8:def 5 :: thesis: ( M1 is invertible & M2 * M1 = ((M1 ~) * (M1 * M2)) * M1 )

( len M1 = n & width M1 = n ) by MATRIX_0:24;

then ((M1 ~) * (M1 * M2)) * M1 = (((M1 ~) * M1) * M2) * M1 by A1, MATRIX_3:33

.= ((1. (K,n)) * M2) * M1 by A3, MATRIX_6:def 2

.= M2 * M1 by MATRIX_3:18 ;

hence ( M1 is invertible & M2 * M1 = ((M1 ~) * (M1 * M2)) * M1 ) by A2; :: thesis: verum